2021
DOI: 10.1002/ejhf.2346
|View full text |Cite
|
Sign up to set email alerts
|

Circulating heart failure biomarkers beyond natriuretic peptides: review from the Biomarker Study Group of the Heart Failure Association (HFA), European Society of Cardiology (ESC)

Abstract: New biomarkers are being evaluated for their ability to advance the management of patients with heart failure. Despite a large pool of interesting candidate biomarkers, besides natriuretic peptides virtually none have succeeded in being applied into the clinical setting. In this review, we examine the most promising emerging candidates for clinical assessment and management of patients with heart failure. We discuss high-sensitivity cardiac troponins (Tn), procalcitonin, novel kidney markers, soluble suppressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 85 publications
(99 citation statements)
references
References 222 publications
1
78
0
4
Order By: Relevance
“…IL-33 was thought to exert beneficial actions via ST2L that are related to cardiac repair or attenuation of adverse cardiac remodeling ( 15 ). Acting as a soluble truncated form of ST2L, sST2 functions as a decoy receptor for IL-33 and thereby attenuates beneficial effects of IL-33/ST2L signaling in the context of the heart ( 18 ). Previous clinical and experimental studies showed a strong correlation between ST2 and HF ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…IL-33 was thought to exert beneficial actions via ST2L that are related to cardiac repair or attenuation of adverse cardiac remodeling ( 15 ). Acting as a soluble truncated form of ST2L, sST2 functions as a decoy receptor for IL-33 and thereby attenuates beneficial effects of IL-33/ST2L signaling in the context of the heart ( 18 ). Previous clinical and experimental studies showed a strong correlation between ST2 and HF ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, natriuretic peptides are elevated also in other conditions, such as ischaemic heart disease and pulmonary embolism, not being a specific HF biomarker [71,72]. Baseline high sensitivity cardiac troponin T and its increase are associated with mortality, disease worsening and acute decompensation, in HF patients [72][73][74][75][76][77][78][79]. Sensitive contemporary cardiac troponin I is also a predictive biomarker of all-cause and cardiovascular mortality, in HF outpatients [73].…”
Section: Heart Failure Pathophysiology Paradigm: What Is Beyond Left ...mentioning
confidence: 99%
“…Interestingly, GDF15 levels have been reported to be elevated in patients with HF and negatively associated with clinical outcome and mortality [ 24 , 25 , 26 , 27 ]. Higher levels of GDF15 were found in patients with HF who were older and with higher New York Heart Association functional class and had lower body mass index and exercise capacity [ 27 ].…”
Section: Introductionmentioning
confidence: 99%